No Loitering: A Response to Disha et al. on Medical Assistance in Dying’s 90-day Assessment Period - Christopher Lyon (Canadian Journal of Bioethics)
Disha et al., in their 2023 paper in this journal, interchangeably frame the Canadian Criminal Code’s 90-day assessment period safeguard for Medical Assistance in Dying (MAID) for people without a foreseeable natural death (Track 2) as a “waiting”, “reflection”, and “assessment” period. However, the law and formal guidance explicitly describe its purpose as an assessment period, only incidentally a reflection period, but not a waiting period. Accordingly, there is an urgent ethical, practical, and legal need to ensure MAID practitioners, their colleagues, and overseers rigorously understand and apply the law to protect patients’ lives from transgressions and stop transgressors.